Optimizing digital technologies in Sharia-compliant education: a contextual model for ICT integration in Aceh’s madrasahs - Jihad, Afdhal (Institute of Computer Science (IOCS), 2025)
The utilization of digital technology has become pivotal in enhancing the quality of education, particularly in madrasahs, which play a crucial role in shaping students' character and competencies. This study explores the optimization of digital technology for the development of madrasah students through innovative learning and nurturing practices within the Sharia-compliant context of Aceh. A qualitative descriptive method was employed to collect and analyze data through interviews, observations, and document analysis, supported by a quantitative approach using a modified MOORA method to objectively evaluate visual learning components. The qualitative analysis involved coding, thematic categorization, and data triangulation to identify patterns in technology-based learning practices and their integration with Islamic values. The quantitative phase normalized decision matrix values and computed preference scores to rank alternative visual designs. Findings reveal that digital technology enhances teacher-student interaction, supports adaptive learning, and strengthens parental engagement, all while upholding Islamic principles. The study emphasizes the need for teacher training, Islamic-based digital content, and policy support to ensure sustainable and Sharia-compliant technology adoption in Aceh's madrasahs.